Gastroesophageal reflux disease (GERD): back to surgery? - Krähenbühl, Lukas; Büchler, Markus W.; Frei, E.; Klaiber, Christian (Progress in surgery, 1997)
This volume provides a detailed and comprehensive review of current knowledge concerning all aspects of gastroesophageal reflux disease (GERD). The opening chapters on its pathogenesis and epidemiology include discussions of Helicobacter pylori as an etiological agent, and Barrett’s esophagus. The bulk of the volume is taken up with critical reviews of all the contemporary approaches to GERD - both medical and surgical (open and laparoscopic) - and presents the early results from laparoscopic trials throughout the world. The book concludes with detailed descriptions from expert practitioners of the various alternative laparoscopic fundoplication techniques. This timely publication will be of interest not only to gastroenterologists and gastrointestinal surgeons, but to all doctors and general practitioners who must advise and prescribe treatment for patients with this common, distressing, but remediable complaint.